[Geertz, Armin W.; Sinding Jensen, Jeppe, ed. Religious narrative, cognition, and culture: image and word in the mind of narrative] - Bahna, Vladimír (Religio, 2013)
Geertz, Armin W.; Sinding Jensen, Jeppe, ed. Religious narrative, cognition, and culture: image and word in the mind of narrative. Sheffield; London; Oakville (CT): Equinox Pub. Ltd., 2011. x, 336 s. ISBN 978-1-84553-295-6.